Sinagoge pada Masa Intertestamental dan Relevansinya dengan Gereja Masa Sekarang - Stanley Santoso (Jurnal Teologi Berita Hidup, 2020)
Abstract:            The synagogue is parallel to the word congregation, which initially means a place to study together, but then refers to a group of people and finally applies to the building where the congregation gather, which then develops to the institutional life of the Jewish church. The synagogue began during the exile, because of the Jewish desire to worship Yahweh, but they were scattered in exile and far from the temple, but they continued to remember God's promises and had hopes of returning to worship in the temple. Synagogues developed during the intertestamental period.            Worship in the Synagogue focuses on prayer and studying the Scriptures. The main form of worship is reading and studying the Scriptures. The synagogue was the most important institutional development in Judaism which also involved Christian origins. The synagogue became a place for the teachings of Jesus and then His apostles, and which later gave birth to early Christian converts. The synagogue is the initial model of the church system.Abstrak:            Sinagoge sejajar dengan kata jemaat, yang pada awalnya sesuai berarti tempat untuk belajar bersama, namun kemudian merujuk kepada kumpulan orang dan akhirnya diterapkan pada bangunan yang menjadi tempat jemaat berkumpul, yang kemudian berkembang kepada kehidupan institusional jemaat Yahudi. Sinagoge bermula pada masa pembuangan, karena kerinduan orang Yahudi untuk beribadah kepada Yahweh, namun mereka tersebar di pembuangan dan jauh dari bait suci, tetapi mereka terus mengingat janji Allah dan memiliki pengharapan akan kembali beribadah di bait suci. Sinagoge berkembang pada masa intertestamental.            Ibadah dalam Sinagoge berfokus pada doa dan mempelajari Kitab Suci. Bentuk utaman ibadahnya adalah pembacaan dan mempelajari Kitab Suci. Sinagoge merupakan perkembangan institusional yang paling penting dalam Yudaisme yang juga menyangkut asal-usul Kristen. Sinagoge menjadi tempat bagi pengajaran Yesus dan kemudian para rasulNya, dan yang kemudian melahirkan para petobat Kristen mula-mula. Sinagoge merupakan model awal dari sistem gereja.